A Late Neoproterozoic age for the Caledonia Mountain Pluton, a high Ti-V layered gabbro in the Caledonia (Avalon) terrane, southern New Brunswick - Barr, Sandra M.; Hamilton, Michael A.; White, Chris E.; Samson, Scott D. (Atlantic Geoscience, 2000)
Gabbro from the Caledonia Mountain Pluton in the northeastern Caledonian Highlands of southern New Brunswick yielded a U-Pb (zircon) crystallization age of 615 ± 1 Ma. The age shows that the Caledonia Mountain Pluton is co-genetic with its host metavolcanic rocks, significantly older than the Mechanic Settlement Pluton, and probably unrelated to the Lower Coverdalc ferrogabhro complex. The chemical characteristics of the pluton are consistent with those of mafic volcanic rocks in the arc-generated Broad River Group, with which the pluton is likely to be co-magmatic. However, the chemical compositions of the gabbroic samples show strong evidence for modification by processes of crystal fractionation and accumulation, and most are unlikely to reflect magmatic compositions. The epsilon Nd value of +3.7 indicates that, like other igneous rocks in the Caledonia terrane, the magma that formed (he Caledonia Mountain Pluton was not derived directly from depleted mantle, but had a component of older crust involved in its petrogenesis, either directly in the source area or by subsequent interaction with crustal materials, Elevated values of Ti, Fe, V, and P in the gabbro suggest that potential may exist for economic deposits, cither in the Caledonia Mountain Pluton or other similar bodies in the Caledonian Highlands RÉSUMÉ On a situé la cristallisation du gabbro du plulon du mont Caledonia dans le nord-est des collines calédoniennes du Sud du Nouveau-Brunswick a 615 ± 1 Ma par datation au U-Pb (à parlir de zircon). Cet âge révèle que le pluton du mont Caledonia est cogénétique avec ses roches métavolcaniques hôtcs, qui sont infiniment plus âgées que Ie pluton de Mechanic Settlement et qui ne sont probablement pas apparentiées au complexe de ferrogabbro de Lower Coverdale. Les caractéristiques chimiques du pluton correspondent à celles des roehes volcanomafiques du groupe formi par un arc de la riviére Broad, avec lequel le pluton est vraisemblablement comagmatique. Les compositions chimiques des échantillons gahbroiques afflchent toutefois des signes marqués de modifications en vertu de processus de fraclionnement el d’accumulation de cristaux. et la majorité ne devraient pas présenter de compositions magmatiques. La valeur de +3.7 epsilon Nd révèle qu à l’instar des autres roehes ignées du terrane de Caledonia, le magma qui a formé le pluton du mont Caledonia ne provenait pas directement du manieau épuisé mais qu’une partie de l’écorce plus &#xE0grée a été mélée à sa pétrogenèse. soit directement dans le seeteur d’origine ou par interaction subséquente avec le matériel crustal. Les valeurs élevées de Ti, de Fe, de V et de P dans le gabbro permettent de supposer qu’il pourrait exisler un potentiel de gites rentables. soit dans le plulon du mont Caledonia, soit dans des massifs analogues a l’intérieur des collinescalédoniennes. Traduit par la rédaction